2015
DOI: 10.5194/acp-15-11729-2015
|View full text |Cite
|
Sign up to set email alerts
|

High ice water content at low radar reflectivity near deep convection – Part 2: Evaluation of microphysical pathways in updraft parcel simulations

Abstract: Abstract. The aeronautics industry has established that a threat to aircraft is posed by atmospheric conditions of substantial ice water content (IWC) where equivalent radar reflectivity (Ze) does not exceed 20–30 dBZ and supercooled water is not present; these conditions are encountered almost exclusively in the vicinity of deep convection. Part 1 (Fridlind et al., 2015) of this two-part study presents in situ measurements of such conditions sampled by Airbus in three tropical regions, commonly near 11 km and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 70 publications
(102 reference statements)
2
47
0
Order By: Relevance
“…Two bulk microphysics schemes and one explicit bin microphysics scheme are evaluated, providing insight into how the bias and its causes differ between fundamentally different approaches to microphysics parameterization. The extent to which a reflectivity bias exists in bin microphysics schemes has not been extensively explored, although Ackerman et al (2015) show that a CRM simulation using bin microphysics failed to reproduce observed low reflectivity values in high-IWC regions, suggesting that this bias may exist across both bulk and bin schemes. Observations are described in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…Two bulk microphysics schemes and one explicit bin microphysics scheme are evaluated, providing insight into how the bias and its causes differ between fundamentally different approaches to microphysics parameterization. The extent to which a reflectivity bias exists in bin microphysics schemes has not been extensively explored, although Ackerman et al (2015) show that a CRM simulation using bin microphysics failed to reproduce observed low reflectivity values in high-IWC regions, suggesting that this bias may exist across both bulk and bin schemes. Observations are described in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…The more numerous particles allow for the particle interaction/collection related to ice phase precipitation formation to occur lower in the atmosphere and earlier in the simulation, delaying sedimentation and increasing vapor competition between particles, which in turn limits the maximum 5 particle size. In the weaker updraft regime of the stratiform region, transported hydrometeors are able to grow more efficiently compared to the stronger updrafts of the convective region, an occurrence which has also been reported in the observations of Ackerman et al (2015). The reduced near surface reflectivity values observed by both Min et al (2009) and Li and Min (2010) suggest that total surface precipitation will be affected by the effects of dusty conditions on cloud dynamics and precipitation PSD, most likely resulting in an overall reduction in surface rain rates.…”
Section: Discussionmentioning
confidence: 57%
“…While ice multiplication from the Hallett-Mossop scheme is active in both cases, removing the depositional-condensation nucleation is sufficient to reduce graupel formation and delay the glaciation of the clouds until temperatures near the homogeneous freezing level 25 where immersion freezing is most active. The observations/modeling studies of Lawson et al (2015) and Ackerman et al (2015) both suggest that this effect on cloud glaciation can be explained by sufficiently fast ice multiplication at warmer temperatures, creating small ice crystals similar to the effects of significantly large deposition-condensation freezing, although it should be noted that primary ice formation was not the focus of those studies and ice nucleation was treated simply, leaving a possible gap in the understanding of the interactions between the ice nucleation and ice multiplication 30 processes. In our simulation the removal of the deposition-condensation freezing greatly hinders the formation of midlevel ice, despite an unchanged IN concentration and active ice multiplication, showing the importance of even small number of midlevel ice formation to the overall vertical hydrometeor distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the liquid water content that freezes does not vary with updraft strength, the freezing of more numerous droplets in the faster updrafts simply produces smaller ice particles. This is clearly shown by Ackerman et al (2015), in which ice particle mass distributions in homogeneous freezing for stronger updrafts produce substantially smaller ice particles. Schnaiter et al (2016) further showed that high ice particle growth rates also enhance the formation of small-scale complexity, such as ice particle surface roughness.…”
Section: The Cloud Chambermentioning
confidence: 64%